A neurophenomenological approach to non-ordinary states of consciousness: hypnosis, meditation, and psychedelics - Timmermann,Slater CB; Bauer,P; Gosseries,O; Vanhaudenhuyse,A; Vollenweider,F; Laureys,S; Singer,T; Mind,and Life MLE ENCECON Research Group; Antonova,E; Lutz,A (Trends in Cognitive Sciences, 2023)
No contemporary unifying framework has been provided for the study of non-ordinary states of consciousness (NSCs) despite increased interest in hypnosis, meditation, and psychedelics. NSCs induce shifts in experiential contents (what appears to the experiencer) and/or structure (how it appears). This can allow the investigation of the plastic and dynamic nature of experience from a multiscale perspective that includes mind, brain, body, and context. We propose a neurophenomenological (NP) approach to the study of NSCs which highlights their role as catalysts of transformation in clinical practice by refining our understanding of the relationships between experiential (subjective) and neural dynamics. We outline the ethical implications of the NP approach for standard conceptions of health and pathology as well as the crucial role of experience-based know-how in NSC-related research and application.